MENANAMKAN AKHLAK MULIA MELALUI PENDIDIKAN AGAMA ISLAM: STUDI KONTEKSTUAL SURAT LUQMAN DI PENDIDIKAN MENENGAH - Kartika, Ika; Arifudin, Opan (Penerbit Lafadz Jaya, 2025)
This research is motivated by the persistent gap between the ideal values taught in Islamic Religious Education (PAI) and student behavior in the school environment. Therefore, a contextual study is needed to examine the meaning of the verses of Surah Luqman and their implementation in secondary education teaching. The purpose of this study is to explore the moral values in Surah Luqman verses 13–19 and examine their implementation in Islamic Religious Education (PAI) teaching at the secondary education level. This study uses a descriptive qualitative approach with data collection techniques through literature studies, interviews with PAI teachers, and observations of classroom teaching practices. The results show that core moral values such as monotheism, respect for parents, honesty, responsibility, patience, and humility have been taught by teachers, but their implementation is still predominantly cognitive and lacks contextualization. Teachers tend to deliver material theoretically without directly linking it to students' real-life experiences. This condition results in the process of internalizing morals not being optimal in shaping students' daily behavior. Therefore, Islamic Religious Education (PAI) teaching needs to be directed towards a more applicable, communicative, and contextual approach so that Quranic values can be instilled more effectively. This study recommends developing Islamic Religious Education (PAI) teaching methods that emphasize the active role of teachers as value facilitators, spiritual companions, and moral role models in secondary education settings.